Effectiveness Combination of Hypnotherapy and Aromatherapy In Reducing Emesis Gravidarum - Contesa, Lina; Sari, Sagita Darma; Rini Anggraeni (International Journal on Health and Medical Sciences, 2023)
More than 50% of 1st trimester pregnancies are accompanied by emesis. Nausea and vomiting in pregnant women is a physiological condition but can have a bad impact if it occurs continuously. The body will become weak, pale and lack fluids so that the blood becomes thick (hemoconcentration). This inhibits the supply of oxygen and nutrients from the mother to the fetus. Emesis can be treated with medication or vitamin B complex or vitamin B6. Non-pharmacological treatments include aromatherapy and hypnotherapy. The aim of this research is to determine the effectiveness of a combination of hypnotherapy and aromatherapy in reducing emesis gravidarum. Quasi experimental research method, one group pre and posttest design. The sample consisted of 30 pregnant women with emesis. Purposive sampling technique. data analysis using the dependent t test. Measuring the nausea scale with the Rhodes index obtained the average nausea and vomiting score before administering the combination aromatherapy and hypnotherapy based on the Rhodes Index in mothers, namely 21.1 and there was a decrease in the score after giving a combination of hypnotherapy and aromatherapy to 18.8. There is a gift effect combination of hypnotherapy and aromatherapy in reducing emesis gravidarum (p-value = 0.001). Based on the research results, it can be concluded administering a combination of hypnotherapy and aromatherapy is effective in reducing emesis gravidarum in first trimester pregnant women.